Evidence-based nursing care for stroke and neurovascular conditions - Alexander, Sheila A. (Ames, Iowa : Wiley-Blackwell, 2013)
With the aging population ever growing, healthcare for persons suffering from stroke and related illnesses is increasingly important. Evidence-Based Nursing Care in Stroke and Neurovascular Conditions provides a comprehensive and practical guide for novice, experienced and advanced practice nurses working with patients suffering from stroke and other neurovascular conditions. With a focus specifically on neurovascular disorders, this highly detailed text offers easy-to-find information on evidence-based care guidelines. The book begins with a thorough introduction to normal.
5 Subarachnoid HemorrhagePATHOPHYSIOLOGY; PREVENTION; DIAGNOSIS; ACUTE CARE; Aneurysm securement; Post-operative care; AVM securement; Support of hemodynamic stability; Hydrocephalus; Hyponatremia; Cerebral edema; LONG-TERM CARE; REFERENCES; 6 Cerebral Amyloid Angiopathy; DEFINITION; HISTORICAL PERSPECTIVE; EPIDEMIOLOGY; PATHOPHYSIOLOGY; DIAGNOSIS; Clinical diagnostic criteria; Associated diagnoses; CAA COMPLICATIONS; Intracerebral Hemorrhage; Use of antithrombotic agents; Anticoagulation therapy; Hypertension; DRUG RESEARCH AND DEVELOPMENT; Summary and conclusions; REFERENCES.
Edition statement from running title area.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed May 21, 2013).
Keywords: Cerebrovascular disease -- Treatment; Evidence-based nursing; Cerebrovascular Disorders -- nursing; Evidence-Based Nursing -- methods; Cerebrovascular disease -- Treatment; Cerebrovascular disease; Stroke; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); MEDICAL -- Neurology; Cerebrovascular disease -- Treatment; Evidence-based nursing; Electronic books